Predictors of Bullying and Victimisation in Children with Attention-Deficit/Hyperactivity Disorder - Anamarija Žic Ralić; Daniela Cvitković; Snježana Sekušak-Galešev (Center for Educational Policy Studies Journal)
The objective of this paper is to determine whether age, gender, Individualised Education Programme, the experience of victimisation by peers, and the experience of bullying others are predictors of bullying and victimisation in children with ADHD. The sample consisted of children aged from 7 to 15 with ADHD diagnosis (N=72). Gender is a significant predictor of physical bullying, whereas the predictors of verbal bullying are gender, being enrolled in an Individualised Education Programme (IEP), verbal victimisation and the feeling of security. The males with ADHD without any school accommodations (IEP) and who are exposed to verbal victimisation are also more often verbally aggressive towards their peers. Children with ADHD who are verbally aggressive and feel secure in the school setting are more exposed to verbal victimisation.